STRATEGI KOMUNIKASI PEMBELAJARAN BAHASA INGGRIS UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA DI SMPIT NURUL ISLAH BANDA ACEH - rina syafitri (Universitas Teuku Umar, 2018)
Education is a very important element to create quality human resources.Learning is doneevery day of the week starting from morningtill night for six months more quickly proven to helptheir improve their languageskills. By using the communication strategy learning in teachingand learning in the SMPIT Nurul Ishlah. The purpose of this study was to determine thelearningstrategies used in the the SMPIT Nurul Ishlah Banda Aceh, teacher communicationprocess with thestudents in learning English, and know the communication media used inteachingand learning in the SMPIT Nurul Ishlah Banda Aceh.This study uses qualitativeresearch methods with the presentation of analysisdesktriptif. The informants are teachers aslecturers and students of Englishvillages were selected purposively. Data collection techniquesused wereobservation, interviews, and documentation. The validity of the technique used inthisresearch is triangulation and extension of participation. In analyzing the data, the researcherused the Constant Comparative Method.The results of the research is shown that students in theSMPIT Nurul Ishlah at learning procesess applied communication strategies by doing classinstruction, word coinage, codeswitching, and appeal for help, without the knowing. That washapped autonomous.Keywords : Communication Strategy,English, SMPIT Nurul Ishlah, Teaching